Effect of cardboard shelter traps on predation of diaspidid scale insects by european earwigs Forficula auricularia in kiwifruit - Logan, D.P.; Maher, B.J.; Connolly, P.G.; Pettigrew, M.J. (New Zealand Plant Protection, 2007)
European earwigs Forficula auricularia L are important predators of diaspidid scale insects in New Zealand kiwifruit As European earwigs readily hide during the day in shelter traps made of corrugated cardboard strips rolled into cylinders it may be possible to manipulate the level of scale predation The effect of trapping duration on aggregation of earwigs and whether the addition of shelter traps to kiwifruit vine canopies led to increased numbers of earwigs and predation of scale insects were investigated More earwigs were found in cardboard shelter traps exposed for up to 8 weeks than shorter periods However shelter traps were not associated with increased numbers of earwigs in vine canopies or with increased predation of scale insects Predation of scale insects was 7382 and on individual canes depended on the initial density of scale Further study is needed to realise the potential of earwigs as predators of scale insects and other pests